2019
DOI: 10.1111/pedi.12874
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Arterial Damage in Children and Adolescents with Type 1 Diabetes: A Systematic Review and Meta‐Analysis

Abstract: Background and Objective Type 1 diabetes is an important risk factor for the development of cardiovascular disease. Pulse wave velocity (PWV) and carotid intima‐media thickness (cIMT) measurements are well recognized as independent predictors for future cardiovascular disease. The aim of the present study was to systematically review the literature and conduct a meta‐analysis assessing measures of subclinical arterial damage in children and adolescents with type 1 diabetes in comparison to healthy controls. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 47 publications
6
29
1
2
Order By: Relevance
“…The lack of difference between groups at baseline in the cardiovascular measures may be partly attributable to the similarity in age, lean body mass, physical activity, and cardiorespiratory fitness between groups. In contrast to our findings, arterial compliance, measured as PWV and AIx75, was reported to be elevated in some, though not all, studies of adolescents with T1D . Appearance of vascular changes in T1D may vary by site and method of measurement and can be impacted by age and sex.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The lack of difference between groups at baseline in the cardiovascular measures may be partly attributable to the similarity in age, lean body mass, physical activity, and cardiorespiratory fitness between groups. In contrast to our findings, arterial compliance, measured as PWV and AIx75, was reported to be elevated in some, though not all, studies of adolescents with T1D . Appearance of vascular changes in T1D may vary by site and method of measurement and can be impacted by age and sex.…”
Section: Discussioncontrasting
confidence: 99%
“…Arterial compliance is a predictor of cardiovascular disease and mortality. Arterial compliance is often, though not always, reduced in adolescents with T1D . The autonomic nervous system regulates heart rate and vascular tone and is also impacted by T1D.…”
Section: Introductionmentioning
confidence: 99%
“…The most common method for assessing these early subclinical manifestations are through the use of surrogate markers such as increased arterial wall thickness (carotid intima-media thickness, cIMT), accelerated arterial stiffening (pulse wave velocity, PWV), or endothelial dysfunction (flow mediated dilation, FMD) ( 15 , 29 ). A recent systematic review and meta-analysis including 23 studies on cIMT and carotid-femoral PWV showed higher cIMT and PVW in youth with T1D than matched controls ( 30 ).…”
Section: Adolescence Is a Critical Time For The Onset Of Cardiovascular Diseasementioning
confidence: 99%
“…La mayoría de las recomendaciones se basa en consensos de expertos y en estudios de cohorte. El tratamiento agresivo de los múltiples factores de riesgo cardiovascular es la clave para mejorar los resultados a largo plazo 69,77,78,79 .…”
Section: Otros Factores Consideradosunclassified